An Efficient Multiplex PCR-Based Assay as a Novel Tool for Accurate Inter-Serovar Discrimination of Salmonella Enteritidis, S. Pullorum/Gallinarum and S. Dublin - Xiong, Dan (Front Microbiol, 2017)
Salmonella enterica serovars Enteritidis, Pullorum/Gallinarum, and Dublin are infectious pathogens causing serious problems for pig, chicken, and cattle production, respectively. Traditional serotyping for Salmonella is costly and labor-intensive. Here, we established a rapid multiplex PCR method to simultaneously identify three prevalent Salmonella serovars Enteritidis, Pullorum/Gallinarum, and Dublin individually for the first time. The multiplex PCR-based assay focuses on three genes tcpS, lygD, and flhB. Gene tcpS exists only in the three Salmonella serovars, and lygD exists only in S. Enteritidis, while a truncated region of flhB gene is only found in S. Pullorum/Gallinarum. The sensitivity and specificity of the multiplex PCR assay using three pairs of specific primers for these genes were evaluated. The results showed that this multiplex PCR method could accurately identify Salmonella Enteritidis, Pullorum/Gallinarum, and Dublin from eight non-Salmonella species and 27 Salmonella serovars. The least concentration of genomic DNA that could be detected was 58.5 pg/μL and the least number of cells was 100 CFU. Subsequently, this developed method was used to analyze clinical Salmonella isolates from one pig farm, one chicken farm, and one cattle farm. The results showed that blinded PCR testing of Salmonella isolates from the three farms were in concordance with the traditional serotyping tests, indicating the newly developed multiplex PCR system could be used as a novel tool to accurately distinguish the three specific Salmonella serovars individually, which is useful, especially in high-throughput screening.